KORELASI STATUS GIZI DAN DURASI DIARE PADA BALITA DENGAN DIARE AKUT DI RUANG RAWAT INAP ANAK RSUD ARIFIN ACHMAD PROVINSI RIAU - Ekky Wibisono; Dedi Satriya Putra; Dewi Anggraini (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTDiarrhea emerges as the developing countries major cause of mortality and morbidity in children under five years especially in Indonesia. Malnutrition and infection well-known have directionally related. Malnutrition was able to be predisposing factor of infection especially enteric infection. Malnourished children had increased risk to have a worse or longer diarrheal duration more than normal children of nutritional status. This study aimed to describe correlation between nutritional status and diarrheal duration in children under five years of age in the Pediaetric Unit of Arifin Achmad General Hospital of Riau Province. This study was found 30 hospitalized childrens under five years with acute diarrhea whom 53,3% were 0-12 years old, 53,3% were males, 80,0% had normal Z-score, 86,7% with mild dehydration, 93,3% length of stay < 5 days and 53,3% diarrheal duration 4-7 days. Sommer’s d test had shown r = 0,044 and p value = 0,772. There was no significant association between nutritional status and diarrheal duration in hospitalized children under five years of age with acute diarrhea in Arifin Achmad General hospital of Riau ProvinceKeywords: acute diarrhea, children under five years, duration, nutritional status